An Immunohistochemical Study Of Survivin Expression In Normal And In Transformed Cells - Alias, Iskandar Zulkarnain (2006)
Survivin is a new member of the inhibitors of apoptosis protein (IAP) family, selectively over-expressed in common human cancers but not in normal adult tissues. It is also expressed in cancer cell lines. The study was performed generally to investigate the basic and clinical roles of survivin in normal and transformed cells. Rabbits were immunized with two synthetic oligopeptides, MGAPTLPPAWQP and KEFEETAKKVRRAIEQLAAMD amino acids sequences of the survivin molecule.